ANALISIS POTENSI SEKTOR EKONOMI KABUPATEN BLITAR DAN KABUPATEN TULUNGAGUNG - Anisa Himayanti Putri; Sri Muljaningsih (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The purpose of this study is to find potential sectors owned by the region and to determine the effect of the basic and non-base sectors on economic growth in Blitar and Tulungagung districts. Including quantitative descriptive research and using secondary data. Analysis technique with Location Quotient, Shift Share, Klassen Typology, and Multiple Linear Regression. The data used are Gross Regional Domestic Product at Constant Prices in 2013 to 2020 Blitar Regency, Tulunggagung Regency and East Java Province, Economic growth rate in 2013-2020 Blitar Regency and Tulungagung Regency. The results of this study are that Blitar Regency has a trade sector and transportation sector as one of the potential sectors and Tulungagung Regency has a processing industry sector and a water supply, waste management, waste and recycling sector. The basic and non-base sectors have a positive and significant impact on economic growth in the two districts. Through this study, it helps the government to pay more attention to the potential sectors owned by the region and to maximize its economic development.